Revenue Increase for Water Utilities from Improved Metering— An Empirical Analysis of an Installation Project in Livingstone, Zambia - Dai, Yuji. (2017)
Abstract: Water utilities in developing countries are progressively moving towards automatic meter reading (AMR) technology in an attempt to deal with revenue losses from both technical and non-technical issues associated with analog meters. Technically, the accuracy of AMR meters avoids meter reader mistakes; non-technically, AMR meters reduce the possibilities of shirking or corruption. AMR meters thus in turn affect customer consumption and payment decisions. As the availability of evidence on utilities' revenue increase from AMR meters is limited, this study fills the gap by testing the impact of installation of AMR meter in the context of a regional water utility in Zambia. The difference-in-difference design shows that the use of AMR meters increases households' billed water quantities. Customer payment amounts are in excess of the increases in amount billed. The estimated results are then used to calculate the justified upfront investment in water metering system.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Kelsey Jack.; Committee: Mary Davis.; Keyword: Economics.